2020
DOI: 10.1002/mus.27091
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term survival of participants in the CENTAUR trial of sodium phenylbutyrate‐taurursodiol in amyotrophic lateral sclerosis

Abstract: An orally administered, fixed-dose coformulation of sodium phenylbutyratetaurursodiol (PB-TURSO) significantly slowed functional decline in a randomized, placebo-controlled, phase 2 trial in ALS (CENTAUR). Herein we report results of a long-term survival analysis of participants in CENTAUR. In CENTAUR, adults with ALS were randomized 2:1 to PB-TURSO or placebo. Participants completing the 6-month (24-week) randomized phase were eligible to receive PB-TURSO in the open-label extension. An all-cause mortality an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
104
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 139 publications
(122 citation statements)
references
References 34 publications
1
104
0
Order By: Relevance
“…Therefore, compounds acting against neuroinflammation can also show efficacy. Some interesting options are: a) masitinib, a tyrosine kinase inhibitor, which is predicted to work by decreasing microglia-induced inflammation of MNs in the brain and spinal cord [146] (NCT02588677); b) a combination of sodium phenylbutyrate and tauroursodeoxycholic acid (AMX0035), which may limit cell death and neuroinflammation (NCT03127514, NCT03488524, NCT04516096) [147], and c) cyclic nucleotide phosphodiesterase (PDE) inhibitors to prevent glial cell activation (e.g., ibudilast, NCT02238626 IBU-ALS-1201, NCT04057898 COMBAT-ALS). Interestingly, ibudilast also enhances the autophagy-mediated clearance of ALS-associated TAR DNA-binding SOD1 and TDP-43 aggregates [148].…”
Section: Targeting Mitochondria As a Therapymentioning
confidence: 99%
“…Therefore, compounds acting against neuroinflammation can also show efficacy. Some interesting options are: a) masitinib, a tyrosine kinase inhibitor, which is predicted to work by decreasing microglia-induced inflammation of MNs in the brain and spinal cord [146] (NCT02588677); b) a combination of sodium phenylbutyrate and tauroursodeoxycholic acid (AMX0035), which may limit cell death and neuroinflammation (NCT03127514, NCT03488524, NCT04516096) [147], and c) cyclic nucleotide phosphodiesterase (PDE) inhibitors to prevent glial cell activation (e.g., ibudilast, NCT02238626 IBU-ALS-1201, NCT04057898 COMBAT-ALS). Interestingly, ibudilast also enhances the autophagy-mediated clearance of ALS-associated TAR DNA-binding SOD1 and TDP-43 aggregates [148].…”
Section: Targeting Mitochondria As a Therapymentioning
confidence: 99%
“…4-Phenylbutyrate (PBA) and tauroursodeoxycholic acid (TUDCA) are hydrophobic chemical chaperones whose proposed mechanisms of action involve their ability to interact with exposed hydrophobic regions in misfolded or unfolded proteins. Both of these chemical entities are orally bioavailable, have reasonable blood-brain barrier permeability with a no-to-low toxicity profile [112,113], have been used successfully in preclinical models for protein folding diseases [114,115], and are currently being evaluated in clinical trials for ALS [112,113,116,117]. Although plasma cell differentiation and antibody production are not dependent on SIL1 [75], MSS-derived LBLs that are deficient for SIL1 were more prone to cell death than normal controls when treated with tunicamycin, an ER stressor [118].…”
Section: Chemical Chaperonesmentioning
confidence: 99%
“…In addition, recent reporting from a phase II double-blind placebo-controlled trial, the CENTAUR trial, shows the potential of targeting the ER stress pathway for the treatment of neurodegenerative diseases [ 115 , 116 ]. The CENTAUR trial tested the combination of sodium phenylbutyrate and taurursodiol in ALS patients.…”
Section: Clinical Evidence Of Er Stress Modulation As Treatmentmentioning
confidence: 99%
“…Taurursodiol, also known as tauroursodeoxycholic acid helps to prevents apoptosis due to its role in the BAX pathway by preventing translocation of the BAX protein into the mitochondria [ 119 ]. The trial showed slowing of functional decline and increased survival in ALS patients, but longer and larger trials are necessary to further verify the efficacy of this combination [ 115 , 116 ]. These results are very encouraging and support drug development for neurodegeneration by manipulating the ER stress pathway.…”
Section: Clinical Evidence Of Er Stress Modulation As Treatmentmentioning
confidence: 99%